Characteristics of will as predictors of risk inclination of military university students in the process of professional military socialization - Denis A. Meshcheryakov (Saratov State University, 2021)
One of the important and relevant problems of social psychology is the study of the role of will characteristics as important regulators of risk behavior. It is especially interesting to investigate it in such a specific social group as military personnel, whose activities are associated with risk both directly and indirectly. In view of this, the purpose of the research presented in the article is to study changes in volitional determina-tion of risk and rational behavior of the militar y universit y students in the process of professional militar y socialization. As a hypothesis, we suggest that different volitional characteristics mainly determine risk behavior and behavior associated with rationality. The research involves 182 military students (aged M = 20.5; SD = 1.6) of Saratov Military Institute of the National Guard of the Russian Federation. We used the following techniques to analyze changes in volitional determination of rational and risk behavior: the technique for diagnosing the manifestation of volitional personality traits "Volitional personality traits" (M. V. Chumakov); "Risk-taking" questionnaire (A. M. Schubert); the technique for diagnosing two personal-ity traits - readiness for risk and rationality - as psychological variables reflecting the characteristics of personal regulation of the subject's choices (such as decision-making) in the broad context of life situations "Personality factors of decision making" (T. V. Kornilova). We revealed the complication of the volitional determination of rational and risk behavior in the process of professional military socialization; we also found major volitional personality traits, that are predictors of readiness for risk and rationality. It is shown that 8% of variations in rational behavior are due to purposefulness and initiative, and 8% of variations in risk behavior are due to persistence. The study of the identified parameters can help in determining the inclination to risk and rationality of military personnel, their influence on behavior in the course of performing service and combat missions and, consequently, on their more effective and high-quality performance.